The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1108/jfc-08-2018-0089
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between foreign aid and corruption: a case of selected Asian countries

Abstract: Purpose The purpose of this study is to examine the effect of foreign aid (FA) on corruption in selected Asian countries (Pakistan, India, Srilanka and Bangladesh) using the panel data from 2000 to 2014. Design/methodology/approach The author used Levin-Lin-Chu and Im-Pesaran-Shin panel unit root tests to check the stationary properties of the variables. The Pedroni’s and Kao panel cointegration approach was applied to analyze the variable’s long-run relationship. The author used panel dynamic ordinary least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 48 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…To estimate sample data, this study applied a panel data econometric approach. Baltagi (2009) and Ali et al (2019a) suggest that panel data provide several benefits over time series data set and increase the overall efficiency of the regression model. Additionally, the problem of heterogeneity and collinearity among the variables is reduced in panel data sets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To estimate sample data, this study applied a panel data econometric approach. Baltagi (2009) and Ali et al (2019a) suggest that panel data provide several benefits over time series data set and increase the overall efficiency of the regression model. Additionally, the problem of heterogeneity and collinearity among the variables is reduced in panel data sets.…”
Section: Methodsmentioning
confidence: 99%
“…Corruption also considered as a threat to the security and stability of an economic environment and undermined the justice process (Transparency International, 2017). In developing countries, corruption is more prominent and has been a common concern (Ali et al , 2019a; Iqbal and Seo, 2008; Tanzi, 1998; Ali et al , 2019b). Globally, corruption has attained significant attention owing to its adverse impact on the economic system and societies (Zheng, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, FA essentially affects the institutional policies, resulting in more corruption in recipient counties, which inevitably restrains economic growth. Ali et al (2019) examined the relationship between FA and corruption in Asian nations and revealed a remarkable negative effect on the corruption perception index in the recipient countries, showing that more FA results in more corruption. This finding is supported by Brautigam and Knack (2004) and Economides, Kalyvitis and Philippopoulos (2008).…”
Section: Related Literaturementioning
confidence: 99%
“…Subsequently, the growing of the economy in a recipient country will increase the household income, which may contribute to residential life health and consequently decrease health poverty. The government will also use a certain amount of the aid for public expenditures and infrastructure in order to drive the national economy (∆Aid fg i,t > 0), which will eventually improve the national living standards, including medical treatment, although in institution-deficient countries, a considerable amount of aid is kept by the government (Ali et al 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Meanwhile, evidence of local corruption can be seen in ongoing Chinese projects. A study conducted by Ali et al (2019) in Asia assessed the effect of foreign aid on corruption in Bangladesh, India, Pakistan, and Sri Lanka using dynamic ordinary least squares (DOLS) and fully modified ordinary square (FMOLS) panels. The result showed that foreign aid can reduce corruption perception in these countries, but corrupt practices can still persist in its implementation.…”
Section: Foreign Aid and Corruptionmentioning
confidence: 99%